2001
DOI: 10.1038/sj.jea.7500172
|View full text |Cite
|
Sign up to set email alerts
|

Acute health effects of organophosphorus pesticides on Tanzanian small-scale coffee growers

Abstract: Acute health effects of organophosphorus ( OP ) pesticides on coffee farmworkers in 1991 -1992 in Tanzania are reported to provide a basis for concern over farmworkers being overexposed during application. Workers exposed to OP pesticides ( N = 133 ) were drawn from a population of about 240,000 coffee farmers. They were interviewed on symptoms and personal protection, and their erythrocyte acetylcholinesterase ( AChE ) activity was determined during both spraying and nonspraying period. AChE activities durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 9 publications
5
37
0
1
Order By: Relevance
“…Moreover only a few used organophosphates and carbamates which are the ones responsible for the most acute toxic symptoms. The main symptoms reported were skin irritation, headache, extreme tiredness, excessive sweating, blurred vision and dizziness which are consistent with other studies [13,14,15,32]. Many of these symptoms could, however, also be due to other factors like hot climate, long exposure to sunlight or other diseases [31].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Moreover only a few used organophosphates and carbamates which are the ones responsible for the most acute toxic symptoms. The main symptoms reported were skin irritation, headache, extreme tiredness, excessive sweating, blurred vision and dizziness which are consistent with other studies [13,14,15,32]. Many of these symptoms could, however, also be due to other factors like hot climate, long exposure to sunlight or other diseases [31].…”
Section: Discussionsupporting
confidence: 78%
“…al. in Northern Tanzania, close to the border of Uganda, has shown a low quantity of class I pesticides; while a study made in Ghana indicates that small-scale farmers mainly used class II and III pesticides [32,4]. These studies suggest that African small-scale farmers are not as exposed to class I pesticides as Asian and Latin American farmers.…”
Section: Discussionmentioning
confidence: 91%
“…In the 1990s, the frequency of respiratory symptoms reported by 133 farmers in Tanzanian coffee plantations was comparable between spraying and nonspraying periods of organophosphate insecticide [42]. In 2003, no difference in the frequency of respiratory symptoms was observed between 100 pilots performing aerial application of agricultural pesticides in the USA and 100 unexposed matched controls [43].…”
Section: Studies On Agricultural Workersmentioning
confidence: 89%
“…Available data demonstrating unsafe pesticide handling practices in Tanzania suggest a high potential for human exposure, with the highest risk of occupational exposures among pesticide sprayers, farmers, and other agricultural workers. Accordingly, previous Tanzanian questionnaire-based studies identified unsafe pesticide use associated with acute pesticide poisoning as a major problem in the farming community [6,7]. Modern pesticides are reported to cause acute health effects in respondents exposed to high doses with unspecific symptoms such as headache, dizziness, respiratory problems, nausea, vomiting and eventually death.…”
Section: Introductionmentioning
confidence: 99%